Dental Caries Experience and Factors among Preschoolers in Southeastern Mexico: A Brief Communication - America Segovia-Villanueva, MSc; Ramon Estrella-Rodriguez, MSc (Blackwell Synergy, 2006)
To examine the association between dental caries prevalence and selected variables in preschool children.